"Better late than never but never late is better", especially in young women. A multicenter Italian study on diagnostic delay for symptomatic endometriosis. (2nd January 2023) - Pino, Ida; Belloni, Gaia Maria; Barbera, Valeria; Solima, Eugenio; Radice, Davide; Angioni, Stefano; Arena, Saverio; Bergamini, Valentino; Candiani, Massimo; Maiorana, Antonio; Mattei, Alberto; Muzii, Ludovico; et al.
Abstract: Purpose: The aim of the study was to assess the length of diagnostic delay of symptomatic endometriosis in Italy and analyse the presence of correlations between the socio-demographic status of patients and the clinical characteristics/type of diagnosis. Materials and methods: This multicenter cross-sectional questionnaire-based study was conducted in 10 tertiary Italian referral centres for diagnosis and treatment endometriosis. A total of 689 respondents with histologically proven endometriosis and onset of the disease with pain symptoms completed an on-line self-reported questionnaire written in their own language (World Endometriosis Research Foundation-Endometriosis Phenome and Biobanking Harmonisation Project-Endometriosis Patient Questionnaire–Minimum) evaluating endometriosis related symptoms, family history of endometriosis and chronic pelvic pain, demographic data, as well as medical, reproductive, and obstetric history. Results: The mean diagnostic delay found was of 11.4 years. The mean time (14.8 years) from symptoms onset to diagnosis was significantly longer among patients aged 9–19 vs patients aged 20–30 (mean 6.9 years, p < 0.001) and patients aged 31–45 (mean 2.9, p < 0.001). No significant association were found between a delayed diagnosis and any of the clinically relevant factors such as the number or severity of the reported symptoms, familiarity, hormonal therapy intake or methodology of diagnosis. Conclusions: The mean diagnostic delay of endometriosis in Italy is about 11 years. The delay can be up to 4 years longer in patients with pain symptoms onset under 20 years. Educating clinicians and patients on pathologic nature of endometriosis related pelvic pain is advisable to reduce waiting time to diagnosis, especially for young women.